Ulama Networks And The Development Of The Syattariyah Sufi Order In Sumatra The Seventeenth To The Twenty-First Century - Nurul Hidayah Harahap; Indriani; Zulfa Hamidah; Sari Febriani (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2026)
The Syattariyah Sufi order is one of the tariqas that played an important role in the development of Islam in Sumatra through networks of scholars and intellectual traditions. Syattariyah scholars functioned not only as practitioners of Sufism, but also as agents of da‘wah, community leaders, and guardians of local intellectual heritage. This study aims to analyze how scholarly networks shaped, strengthened, and reproduced the continuity of the order in Sumatra through teacher disciple relationships, the transmission of knowledge, and socio-religious roles. The method employed is a qualitative-historical approach with library research on Sufi manuscripts, genealogical chains of transmission (sanad), scholarly works, and academic literature. The findings show that the Syattariyah order developed as a regional network of scholars connecting Aceh, Minangkabau, and Palembang through traditional educational institutions, the circulation of manuscripts, and the legitimation of spiritual lineage. This article emphasizes the uniqueness of the Syattariyah order as an institutionalized socio-intellectual system that is adaptive to colonialism and modernity, and remains relevant in shaping local Islamic identity into the contemporary period.